(untitled) (Research, Society and Development, 2024)
Mandibular fractures are common and account for a significant proportion of facial injuries, especially due to the prominent position of the mandible in the face. The choice of surgical method for fixation of these fractures should consider aesthetics and minimization of complications. This article aims to report the case of a 23-year-old patient, victim of a car accident, with bilateral fractures of the mandible: fracture of the body on the right side and fracture of the mandibular angle on the left side. Treatment involved osteosynthesis of the fractures under general anesthesia using a vestibular mandibular approach. Intraoral incisions were made to access and fix the fractures with titanium plates. A transbucal instrument (trocar) was used to fix the fracture in the left mandibular angle, minimizing external scars. The patient had a good postoperative evolution and is being monitored by the team. It was concluded that intraoral access with transbucal trocar is a safe and advantageous technique for osteosynthesis of mandibular fractures, reducing aesthetic and functional complications and providing a satisfactory recovery.